QUALITY OF BROILER CHICKEN EGGS SOAKED IN BETEL LEAF SOLUTION FOR 24 HOURS AT DIFFERENT STORAGE TIMES - E.A., Romari; Wirapartha, M.; Umiarti, A.T. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
This study aims to determine e the quality of broiler chicken eggs soaked in betel leaf (Piper Betle L.) solution for 24 hours at different storage times. The research design used a completely randomized design (CRD) consisting of 5 treatments with 4 replications and each replication used 3 eggs. So the total number of Isa Brown eggs used is 60 eggs. The betle leaves concentration level to be used is 30% (300 gr + 1000 ml water). The treatments given were: P1: Eggs of Isa Brown chicken without soaking in 30% betle leaves solution and without storage (control), P2: Eggs of Isa Brown chicken soaked in 30% betle leaves solution and stored for 7 days, P3: Eggs Isa Brown chicken eggs soaked with 30% betle leaves solution and stored for 14 days, P4: Isa Brown chicken eggs soaked with 30% betel leaf solution and stored for 21 days and P5: Isa Brown chicken eggs soaked with solution betle leaves 30% and stored for 28 days The variables observed included egg weight, yolk index, haught unit, yolk color, pH, and shell thickness. Based on the results of the study, it was shown that storage time had an effect on the quality of broiler chicken eggs. The quality of chicken eggs decreases every week. On the variable egg weight, yolk index, haught unit and egg yolk color (P<0.05). The egg pH variable increased every week (P<0.05). The shell thickness variable had P2 values higher than P1 (control), P3, P4, and P5 with significantly different treatment (P<0.05). Based on the results of the research that has been done, it can be concluded that storage time has an effect on the quality of broiler chicken eggs soaked in betel leaf solution for 24 hours with a concentration level of 30%. The egg weight variable only lasted until the 7th day (P2). IKT variables, shell thickness and yolk color decreased in quality from day 7 (P2). The HU variable until the 21st day is categorized as grade B while the pH variable has increased every week but is still categorized as good.